Pengaruh Kualitas Pelayanan Account Representative, Sanksi Pajak Dan E-Filling Terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Batam Selatan - Syahfitri, Lucy Adha; Ompusunggu, Hermaya (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to determine how individual taxpayer compliance at KPP Pratama batam is influenced by the influence of Account Representative Service Quality, Tax Sanctions and E-Filling taxpayer awareness. The population in this study were 400,034 individual taxpayers registered at KPP Pratama batam. The analytical method in this study is multiple linear regression. The sampling technique uses proportional random sampling, which is calculated using the slovin formula so that a sample size of 100 respondents is obtained.  The data source used is primary data through questionnaires, while the data analysis technique used is multiple linear regression analysis. The results of this study indicate that the Quality of Account Representative Services, Tax Sanctions and E-Filling have a significant effect on Individual Taxpayer Compliance